Oral corrective feedback as a formative assessment in teaching speaking skill - Siti Mahmudah; Pooja Anggunsari (Journal of Research on English and Language Learning (J-REaLL), 2023)
The purpose of this research is to investigate how teachers and students implement OCF in speaking for EFL students. This research aims at figuring out and reviewing the process, the implementation, and the preferences of teaching-learning in the classroom by applying a type of assessment; that is oral corrective feedback (OCF). English needs to have an assessment as it becomes crucial and affects students from the diagnostic test to the final test. Speaking is a skill that needs to be mastered by students, but it has a lot of challenges faced by foreign students. The term assessment means procedural steps conducted in educational systems to interview, observe, construct questions, review students’ work, and respond to students’ work. Assessment is broken down into two types, formative and summative assessment. Formative assessment is done during the teaching-learning process when the class is still running. Meanwhile, summative assessment happens at the end of the learning period, and it is the last judgment of the teachers. One of the formative assessments that is mostly used and applied is feedback. OCF becomes the focus of this research to improve the students’ speaking skills and to minimize their errors. This research applies library research to find out the use of OCF. It can be seen from the teachers’ feedback because the students will get their errors and try to correct them based on the feedback given by the teachers.